Whole Genome Sequencing and Characterization of Multidrug-Resistant (MDR) Bacterial Strains Isolated From a Norwegian University Campus Pond - Finton, Misti D.; Meisal, Roger; Porcellato, Davide; Brandal, Lin T.; Lindstedt, Bjørn-Arne (Frontiers in Microbiology, 2020)
The presence of extended-spectrum β-lactamase (ESBL)-producing bacteria in environmental sources has been reported worldwide and constitutes a serious risk of community-acquired infections with limited treatment options. The current study aimed to explore the presence of these worrisome bacteria in a pond located at the Norwegian University of Life Sciences in Ås, Norway. A total of 98 bacterial isolates survived growth on selective chromogenic media and were identified by 16S rRNA Sanger sequencing. All strains were evaluated for the presence of the most commonly found β-lactamases and ESBLs in clinical settings (blaCTX-M groups 1, 2 and 9, blaCMY, blaSHV, and blaTEM) and carbapenemases (blaIMP, blaKPC, blaNDM, blaOXA, blaSFC1, blaVIM) through multiplex PCR. A total of eight strains were determined to contain one or more genes of interest. Phenotypic resistance to 18 antimicrobial agents was assessed and isolates were subjected to whole genome sequencing through a combination of Oxford Nanopore’s MinION and Illumina’s MiSeq. Results revealed the presence of β-lactamase and ESBL-producing Escherichia coli, Klebsiella pneumoniae, Stenotrophomonas maltophilia and a Paraburkholderia spp. Identified β-lactamases and ESBLs include blaCTX-M, blaTEM, blaCMY, blaSHV and a possible blaKPC-like gene, with both documented and novel sequences established. In addition, two inducible beta-lactamases were found, a class A beta-lactamase (L1) and a cephalosporinase (L2). All strains were determined to be multidrug resistant and numerous resistance genes to non-β-lactams were observed. In conclusion, this study demonstrates that environmental sources are a potential reservoir of clinically relevant ESBL-producing bacteria that may pose a health risk to humans upon exposure.